Evaluating an urban pediatric hospital's scald burn prevention program - Rochelle Thompson; Ross Budziszewski; Autumn D. Nanassy; Loreen K. Meyer; Paul Glat; Brooke Burkey (BMC, 2021)
Abstract Background Over 450,000 individuals are hospitalized with burns annually and roughly 35% are scald burns. Children younger than 5 years of age are at the greatest risk of scald burn injury. Caregiver burn prevention programs have been found to reduce the prevalence of injuries in young children; however, low-income and underserved populations seldomly have access to these programs. The impact of scald burn prevention programs in underserved populations remains unexplored. The objective of the current study was to evaluate the efficacy of a scald burn prevention program at a Level One Pediatric Trauma Center in a low-income, underserved community. Methods Our hospital developed a one-hour scald burn prevention program for caregivers with children 5 years of age or younger. The program educated caregivers on ways to prevent scald burns and create safeguards in their home. Caregivers completed a pre-post survey to measure their ability to identify hot or cold objects, as well as respond to items about their perceptions of the program's utility, their willingness to share it with others, and the likelihood that they would use the information in the future. Data was analyzed using a paired t-test. Results Two-hundred and sixty-nine (N = 269) caregivers participated in the program. Before the program, caregivers could identify potentially hot objects 83.17% of the time, and after the program, they were able to identify these items 92.31% of the time: t (268) = 12.46, p < .001, d = 1.07. Additionally, 95% of caregivers indicated that the program was helpful, 99% stated that they were likely to share this information with others, and 100% indicated that they would use the information from the program. Conclusions Education is a critical component to prevent scald burns. Results indicate that a hospital-led scald burn prevention program can positively impact a caregiver's ability to identify possible scald-burn risks. Providing education to caregivers who typically do not receive this information could lower the prevalence of scald burns not only institutionally, but in communities that are disproportionately impacted by this mechanism of injury.